Personalismo e distância de poder: um estudo de caso em uma empresa brasileira - Sá, Mariana Alcântara de (2012)
The objective of this exploratory study is to discuss the relationship between national culture and organizational culture based on analysis of the cultural trace of personalism and power distance. It is considered that the organization as part of a society, is heavily influenced by culture and therefore it is necessary know it so that, later, can be proposed an appropriate management model to the Brazilian reality. In this sense, employees of one department were interviewed, to identify how these cultural characteristics are presented, and understand how people deal with them. These reflections point to the necessity of establishing a dialectical perspective that encourages the conscious participation of the members of the department, promoting autonomy and cooperation to build the collective good.